Effects of the wrestling + injury prevention program in freestyle wrestlers: a two-arm randomized controlled trial - Bayati, R.; Majelan, A. S.; Zarei, H. (Journal of Orthopaedic Surgery and Research, 2025)
Background To assess the effectiveness of the Wrestling + injury prevention program on incidence of injuries, neuromuscular mechanisms and dynamic balance of freestyle (FS) wrestler.